2017
DOI: 10.1091/mbc.e16-06-0459
|View full text |Cite
|
Sign up to set email alerts
|

p120-catenin regulates VE-cadherin endocytosis and degradation induced by the Kaposi sarcoma–associated ubiquitin ligase K5

Abstract: Endocytosis of VE-cadherin in response to the Kaposi sarcoma E3 ubiquitin ligase K5 is dependent on two membrane-proximal lysine residues but independent of a constitutive endocytosis motif. p120-catenin blocks endocytosis mediated by both motifs, demonstrating that p120 is a master regulator of multiple context-dependent endocytic signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Endothelial HMEC-1 cells that express the K5 ligase by adenoviral transduction induce VE-cadherin ubiquitination and degradation, together with an increased internalization of VE-cadherin. Interestingly, K5-induced internalization of VE-cadherin does not depend on the same motif that drives the constitutive endocytosis of VE-cadherin, but p120 is still able to restrict the action of the K5 ligase, as the overexpression of p120 rescues K5-mediated down-regulation of VE-cadherin [62]. These data further corroborate the idea that the binding of p120 to the cadherin JMD acts as a master guardian of cadherins stability.…”
Section: Studies From Figueroa's Group Implicated Hakai In E-cadherinsupporting
confidence: 74%
See 1 more Smart Citation
“…Endothelial HMEC-1 cells that express the K5 ligase by adenoviral transduction induce VE-cadherin ubiquitination and degradation, together with an increased internalization of VE-cadherin. Interestingly, K5-induced internalization of VE-cadherin does not depend on the same motif that drives the constitutive endocytosis of VE-cadherin, but p120 is still able to restrict the action of the K5 ligase, as the overexpression of p120 rescues K5-mediated down-regulation of VE-cadherin [62]. These data further corroborate the idea that the binding of p120 to the cadherin JMD acts as a master guardian of cadherins stability.…”
Section: Studies From Figueroa's Group Implicated Hakai In E-cadherinsupporting
confidence: 74%
“…One intriguing possibility is that a member of the membrane-associated really interesting new gene-CH family (MARCH) might serve such a function. Indeed, recent data demonstrated that VE-cadherin is a substrate of the human herpesvirus 8 ubiquitin ligase K5, a member of the MARCH family [62]. Endothelial HMEC-1 cells that express the K5 ligase by adenoviral transduction induce VE-cadherin ubiquitination and degradation, together with an increased internalization of VE-cadherin.…”
Section: Studies From Figueroa's Group Implicated Hakai In E-cadherinmentioning
confidence: 99%
“…Second, it is important to distinguish between constitutive, vs regulated, cadherin endocytosis. For example, tyrosine phosphorylation of p120 ctn destabilizes its association with N‐cadherin to promote cadherin endocytosis in migrating astrocytes, while ubiquitination of VE‐cadherin promotes its endocytosis and downregulation in Kaposi sarcoma . Therefore, constitutive endocytosis may be tuned by both physiological and pathologic signals, and it will be essential to determine their functional contributions to tissue dynamics.…”
Section: Concluding Thoughts For the Futurementioning
confidence: 99%
“…In Madin‐Darby canine kidney (MDCK) II cells and human lung carcinomas, the E3 ligase Huwe1 facilitates poly‐Ub‐mediated degradation of the cadherin‐based adhesion mediator T‐cell lymphoma invasion and metastasis 1 (TIAM1), thereby promoting cell migration (Vaughan et al, ). The membrane‐associated really interesting new gene‐CH (MARCH) family E3 ligase, K5, could ubiquitinate vascular endothelial (VE)‐cadherin to promote its endocytosis and lysosomal degradation, thereby resulting in the disruption of endothelial AJs and remodelling of the actin cytoskeleton (Mansouri et al, ); however, p120 may prevent the vascular endothelial cadherin (VE‐cadherin) from taking part in K5 catalysis (Nanes et al, ). In herpes simplex virus 1 (HSV‐1)‐infected cells, the E3 ligase, Cbl, interacts with the cell adhesion molecule, Nectin‐1 to promote its removal from the membrane (Deschamps et al, ).…”
Section: Ubiquitination In Cellular Events Of Epithelial Morphogenesismentioning
confidence: 99%